G391(P) A case report highlighting unusual benign radiological lesions in a hydronephrotic kidney. (27th April 2016) - Tabb, E; Clark, M; Kerecuk, L
Abstract : Aim: A case report to highlight the benign nature of unusual radiological lesions in single functioning hydronephrotic kidneys in patients with chronic kidney disease. This was undertaken in national centre of excellence for renal services and renal transplant centre. Method: At the age of eight years a male patient with a known solitary hydronephrotic kidney and chronic kidney disease stage four had a renal ultrasound following a urinary tract infection. The ultrasound scan showed 'presence of multiple large rounded hyperechoic areas within the renal parenchyma' of the left kidney. This was of concern and therefore an MRI scan was carried out which confirmed four mass like structures in the left kidney of undetermined nature. A renal biopsy was conducted by interventional radiology of the largest of these lesions. Histology was benign and showed mild focal inflammation with fibrosis and tubular atrophy with a degree of glomerulosclerosis. To establish whether this lesion was functioning renal tissue, a DMSA was performed which showed 'good uptake in the regions of the renal mass lesions visualised in the MRI'. In fact, the areas of intervening on the DMSA were poorly functioning which confirmed that the lesions were in fact areas of focal hypertrophied renal tissue. Therefore despite the initial differential diagnosis being lymphoma or malakoplakia, we were confident to say that this was functioning renal tissue. Results: The abnormal radiological lesions were shown to be areas of functional renal tissue with thinning of the rest of the parenchyma. Subsequently we have identified a further three patients have presented with similar radiological appearances and these patients have therefore been prevented from having invasive biopsies and instead have surveillance renal ultrasounds. The patient subsequently developed end stage renal failure 3 years later and now has a functioning renal transplant with the native kidney in situ which has now atrophied. Conclusion: Better resolution of ultrasound scanning showing unusual radiological lesions in hydronephrotic dysplastic kidneys are in fact functioning areas of hypertrophic renal parenchymal tissue, which do not require any further invasive investigations.